The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1109/tsg.2017.2671743
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Forecasting of Price-Responsive Loads Using Inverse Optimization

Abstract: Abstract-We consider the problem of forecasting the aggregate demand of a pool of price-responsive consumers of electricity. The price-response of the aggregation is modeled by an optimization problem that is characterized by a set of marginal utility curves and minimum and maximum power consumption limits. The task of estimating these parameters is addressed using a generalized inverse optimization scheme that, in turn, requires solving a nonconvex mathematical program. We introduce a solution method that ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…In this setting, each market participant solves an optimization problem to determine a bid which they submit to a facilitator, who in turn incorporates the bids in a market clearing optimization problem that determines prices and the consumption or production allocated to each bidder. In this context, the facilitator may impute bidders' right-hand-side constraint parameters, such as bounds on consumption, which can then be used to inform a pricing strategy that aims to maximize profit or control peak demand (Saez-Gallego et al, 2016;Saez-Gallego & Morales, 2018;Xu et al, 2018;Lu et al, 2019). Similarly, a bidder may seek to impute several unknown parameters which can be used in the process of deciding her bid.…”
Section: Motivating Applicationsmentioning
confidence: 99%
“…In this setting, each market participant solves an optimization problem to determine a bid which they submit to a facilitator, who in turn incorporates the bids in a market clearing optimization problem that determines prices and the consumption or production allocated to each bidder. In this context, the facilitator may impute bidders' right-hand-side constraint parameters, such as bounds on consumption, which can then be used to inform a pricing strategy that aims to maximize profit or control peak demand (Saez-Gallego et al, 2016;Saez-Gallego & Morales, 2018;Xu et al, 2018;Lu et al, 2019). Similarly, a bidder may seek to impute several unknown parameters which can be used in the process of deciding her bid.…”
Section: Motivating Applicationsmentioning
confidence: 99%
“…The formulation of an inverse problem for linear programming in [9] took a slightly more general perspective, as it does not assume that the given data necessarily arises as the solution of a linear program, and rather seeks to minimize the distance to the solution set of a linear program. Recent application of the inverse problem for linear programming may be found in [24], for example. These papers on inverse linear programming are foundational and have opened up a great deal of subsequent research.…”
Section: Frommentioning
confidence: 99%
“…Generally, the price-responsiveness of a consumer depends on various factors, e.g., weather conditions, electricity price, time and type of day, and season, etc. [33]. As an example, in [34], it is shown that the response of the load demand has been faster in the cold weather.…”
Section: B Rational End-users (Reus)mentioning
confidence: 99%